Study the Optical and Spectral Properties of Organic Dye as an Effective Medium in Dye Lasers - Afrah M. Al-Hussainey (Journal of Global Pharma Technology, 2018)
In this study, the absorption and fluorine spectra of the Acriflavine solution dissolved in ethanol and different concentrations were studied. The optical properties (absorption coefficient, linear refraction) and spectral properties (Fluorescence lifetime and Quantum Yield fluorescence) were calculated. It is observed that increasing the concentration increases the absorbance values and decreases the permeability values, thus increasing the values of the absorption coefficient and the refractive index. Also, the values of the fluorine intensity increase. The top of the emission spectrum is transferred to the longer wavelengths.Keywords: Acriflavine dye, Absorbance, Fluorescence, Dye Laser.